Seroprevalence of Equine Piroplasmosis in Kelantan - Al-Obaidi QT; M. M. Arshad; Imad Ibrahim Ali Al-Sultan; Mohd Azam Khan Goriman Khan (2014)
Equine Piroplasmosis (EP) is considered as serious disease with implication for international trade. This study was conducted to identify the seroprevalence of T. equi and B. caballi in Kelantan by competitive-inhibition ELISA (c-ELISA). Blood samples were randomly collected from 306 equids (148 horses and 158 ponies) from eight districts of Kelantan, from September 2013 to March 2014. The overall seroprevalence of T. equi, B. caballi and mixed infection were 51.30%, 63.07%, 34.31% respectively. Pasir Puteh and Bachok recorded the highest seroprevalence 92.15% T. equi, 93.22% B. caballi, followed by Pasir Mas and Kota Bharu 68.96% T. equi, 88.46% B. caballi. Machang and Gua Musang showed the lowest seroprevalence 16.66% T. equi, 0.00% B. caballi respectively. In conclusions, the results of this study indicated that EP is widespread in Kelantan.